Research trends and hotspots of post-stroke dysphagia rehabilitation: a bibliometric study and visualization analysis - He, Yuanyuan; Tan, Xuezeng; Kang, Huiqi; Wang, Huan; Xie, Yuyao; Zheng, Dongxiang; Li, Chen (Frontiers in Neurology, 2023)
Background Post-stroke dysphagia (PSD) is one of the most prevalent stroke sequelae, affecting stroke patients’ prognosis, rehabilitation results, and quality of life while posing a significant cost burden. Although studies have been undertaken to characterize the pathophysiology, epidemiology, and risk factors of post-stroke dysphagia, there is still a paucity of research trends and hotspots on this subject. The purpose of this study was to create a visual knowledge map based on bibliometric analysis that identifies research hotspots and predicts future research trends. Methods We searched the Web of Science Core Collection for material on PSD rehabilitation research from its inception until July 27, 2023. We used CiteSpace, VOSviewer, and Bibliometrix R software packages to evaluate the annual number of publications, nations, institutions, journals, authors, references, and keywords to describe present research hotspots and prospective research orientations. Results This analysis comprised 1,097 articles from 3,706 institutions, 374 journals, and 239 countries or regions. The United States had the most publications (215 articles), and it is the most influential country on the subject. “Dysphagia” was the most published journal (100 articles) and the most referenced journal (4,606 citations). Highly cited references focused on the pathophysiology and neuroplasticity mechanisms of PSD, therapeutic modalities, rehabilitation tactics, and complications prevention. There was a strong correlation between the terms “validity” and “noninvasive,” which were the strongest terms in PSD rehabilitation research. The most significant words in PSD rehabilitation research were “validity” and “noninvasive brain stimulation,” which are considered two of the most relevant hotspots in the field. Conclusion We reviewed the research in the field of PSD rehabilitation using bibliometrics to identify research hotspots and cutting-edge trends in the field, primarily including the pathogenesis and neurological plasticity mechanisms of PSD, complications, swallowing screening and assessment methods, and swallowing rehabilitation modalities, and this paper can provide in the follow-up research in the field of PSD rehabilitation. The results of this study can provide insightful data for subsequent studies in the field of PSD rehabilitation.